Cost-benefit analyses of improved forage technologies (Avena altoandina, Arachis pintoi CIAT 22260) in Colombia - CGIAR Research Program on Livestock (2020)
Arachis pintoi CIAT 22160 was developed from accessions available at the CIAT genebank. Avena Altoandina was developed by Agrosavia (Colombian NARS) under the CIAT-Agrosavia agreement "Forages Network of Colombia".